Consciousness Recovery Time of Postoperative Patients with General Anesthesia After Listening Murotal Al-qur’an and Music Therapy - Efa Trisna; Musiana Musiana (Universitas Aisyah Pringsewu, 2022)
After the operation, the patient will experience a process where there is a decrease in the level of consciousness which is called consciousness recovery. This condition will be experienced by patients after surgery with general anesthesia. This condition must be ended immediately for hemodynamic stability. The aim of the study was to see the effect of Al -Qur’an murotal therapy and music on recovery time in postoperative patients. This type of quantitative research uses a quasi-experimental design with a dependent sample t-test. Population and samples were postoperative laparotomy patients under general anesthesia. The result is that there is a difference in the time for consciousness recovery of patients who undergo al-qur'an murotal therapy through audio media with music listening therapy in postoperative Laparotomy patients with general anesthesia. In conclusion, between music therapy and murotal speed the time to recover a fast awake is the murotal of Al-Qur’an. The suggestion is that the murotal therapy is chosen to speed up the time to recover consciousness so that the patient's hemodynamics are stable quickly. Abstrak: Setelah dilakukan operasi pasien akan mengalami proses dimana terjadi penurunan tingkat kesadaran yang disebut pulih sadar. Kondisi ini akan di alami oleh pasien pasca operasi dengan general anaestesi. Kondisi ini harus segera berakhir untuk kestabilan hemodinamik. Tujuan penelitian untuk melihat pengaruh therapy Murotal Alquran dan musik terhadap waktu pulih sadar pada pasien pasca operasi. Jenis penelitian kuantitatif dengan menggunakan rancangan quasi eksperiment dengan uji dependent sample t-test. Populasi dan sampel adalah pasien pasca operasi laparatomi dengan general anaestesi . Hasilnya adalah bahwa ada perbedaan waktu pulih sadar pasien yang dilakukan terapi murotal Al-qur’an melalui media audio dengan terapi mendengarkan musik pada pasien post operasi laparotomi dengan general anestesi. Kesimpulannya, diantara terapi music dan murotal kecepatan waktu pulih sadar yang cepat adalah murotal Al-qur’an .Saran, terapi murrotal Al-qur’an dapat menjadi alternatif terapi yang di pilih untuk untuk mempercepat waktu pulih sadar sehingga haemodinamik pasien kenbali stabil.